Transient nucleation in selective laser melting of Zr-based bulk metallic glass. (October 2020) - Ericsson, A.; Pacheco, V.; Sahlberg, M.; Lindwall, J.; Hallberg, H.; Fisk, M.
Abstract: The crystallization rate during selective laser melting (SLM) of bulk metallic glasses (BMG) is a critical factor in maintaining the material's amorphous structure. To increase the understanding of the interplay between the SLM process and the crystallization behavior of BMGs, a numerical model based on the classical nucleation theory has been developed that accounts for the rapid temperature changes associated with SLM. The model is applied to SLM of a Zr-based BMG and it is shown that the transient effects, accounted for by the model, reduce the nucleation rate by up to 15 orders of magnitude below the steady-state nucleation rate on cooling, resulting in less nuclei during the build process. The capability of the proposed modelling approach is demonstrated by comparing the resulting crystalline volume fraction to experimental findings. The agreement between model predictions and the experimental results clearly suggests that transient nucleation effects must be accounted for when considering the crystallization rate during SLM processing of BMGs. Graphical abstract: Unlabelled Image Highlights: Crystallization in SLM processing of AMZ4 is predicted using a transient nucleation model based on CNT. The nucleation rate is shown to depend on the heating/cooling rate of the temperature cycles in SLM. A diminishing volume fraction is observed at laser powers below 80 W, in agreement with XRD analysis of SLM processed AMZ4. The results suggest that transient nucleation effects play a critical role in promoting glass formation in SLM.